Identification of dendritic cell precursor from the CD11c+ cells expressing high levels of MHC class II molecules in the culture of bone marrow with FLT3 ligand - In, Hyunju; Park, Ji Soo; Shin, Hyun Soo; Ryu, Seul Hye; Sohn, Moah; Choi, Wanho; Park, Sejung; Hwang, Soomin; Park, Jeyun; Che, Lihua; Kim, Tae-Gyun; Chu, Min Kyung; et al. (Frontiers in Immunology, 2023)
Dendritic cells (DCs) are readily generated from the culture of mouse bone marrow (BM) treated with either granulocyte macrophage-colony stimulating factor (GM-CSF) or FMS-like tyrosine kinase 3 ligand (FLT3L). CD11c + MHCII + or CD11c + MHCII hi cells are routinely isolated from those BM cultures and generally used as in vitro-generated DCs for a variety of experiments and therapies. Here, we examined CD11c + cells in the BM culture with GM-CSF or FLT3L by staining with a monoclonal antibody 2A1 that is known to recognize mature or activated DCs. Most of the cells within the CD11c + MHCII hi DC gate were 2A1 + in the BM culture with GM-CSF (GM-BM culture).In the BM culture with FLT3L (FL-BM culture), almost of all the CD11c + MHCII hi cells were within the classical DC2 (cDC2) gate. The analysis of FL-BM culture revealed that a majority of cDC2-gated CD11c + MHCII hi cells exhibited a 2A1 -CD83 -CD115 + CX3CR1 + phenotype, and the others consisted of 2A1 + CD83 + CD115 -CX3CR1 -and 2A1 -CD83 - CD115 -CX3CR1 -cells. According to the antigen uptake and presentation, morphologies, and gene expression profiles, 2A1 -CD83 -CD115 -CX3CR1 -cells were immature cDC2s and 2A1 + CD83 + CD115 -CX3CR1 -cells were mature cDC2s. Unexpectedly, however, 2A1 -CD83 -CD115 + CX3CR1 + cells, the most abundant cDC2-gated MHCII hi cell subset in FL-BM culture, were non-DCs. Adoptive cell transfer experiments in the FL-BM culture confirmed that the cDC2-gated MHCII hi non-DCs were precursors to cDC2s, i.e., MHCII hi pre-cDC2s. MHCII hi pre-cDC2s also expressed the higher level of DC-specific transcription factor Zbtb46 as similarly as immature cDC2s. Besides, MHCII hi pre-cDC2s were generated only from pre-cDCs and common DC progenitor (CDP) cells but not from monocytes and common monocyte progenitor (cMoP) cells, verifying that MHCII hi pre-cDC2s are close lineage to cDCs. All in all, our study identified and characterized a new cDC precursor, exhibiting a CD11c + MHCII hi CD115 + CX3CR1 + phenotype, in FL-BM culture.